Obstacles in the Process of Dealing With Child Sexual Abuse–Reports From Survivors Interviewed by the Independent Inquiry Into Child Sexual Abuse in Germany - Schoon, Wiebke; Briken, Peer (Frontiers in Psychology, 2021)
Barriers in dealing with child sexual abuse (CSA) can hinder survivors in the process of coming to terms with their experiences. The present study aims to identify and analyze factors that may impair the process of dealing with CSA. It is part of a larger research consortium “Auf-Wirkung”, funded by the German Federal Ministry of Education and Research, and was conducted in cooperation with the Independent Inquiry into Child Sexual Abuse in Germany (IICSAG). The IICSAG was appointed by the Independent Commissioner for Child Sexual Abuse Issues and the German Federal Ministry for Family Affairs, Senior Citizens, Women, and Youth in 2016. To determine responsibilities, recognize injustice, and further acknowledge the survivors of CSA in the Federal Republic of Germany (FRG) and the German Democratic Republic (GDR), the Independent Inquiry has held 1,303 private sessions with survivors of CSA by Oct. 17th, 2020. The present study focuses on reoccurring problematic experiences for survivors within the justice system, manipulative offender strategies, and barriers in the provision and quality of mental health care and psychotherapy. Additionally, the role of interpersonal relationships and witness credibility assessment within the context of the rehabilitation process were explored. A total of 30 transcripts of private sessions, conducted by members and appointees of the IICSAG between September 2016 and June 2019, were analyzed using qualitative content analysis. Attendants of private sessions described several barriers, including long term struggles with mental and physical health, reoccurring issues in interpersonal relationships, general financial difficulties, and those linked to redress claims. Limited access to adequate psychotherapy, the lack of transparency of responsible parties, and institutions unwillingness to elucidate occurrences of CSA within their midst, as well as negative social reactions to disclosure, were perceived as obstructive by survivors coping with CSA. In addition to this was the manipulative grooming by perpetrators. Regarding the role of credibility assessment, attendees reported negative experiences in the form of re-traumatization, stigmatization, and insensitive behavior, as well as untrained evaluators and insinuations of therapy-induced memories. Results will be discussed to better support survivors of CSA in their rehabilitation process in the future.